Literature Study of Tempe Bioactive Compounds as Functional Foods in Indonesia - Sinaga, Siska Elisahbet; Tumewu, Zefanya (Universitas Pakuan, 2023)
Tempe is a locally originated food from Indonesia, enriched with numerous bioactive compounds that confer significant health benefits. This review article aims to comprehensively describe the various types of bioactive compounds present in Tempe, elaborate on their functional food roles, and elucidate the ways these compounds contribute to improved health. The methodology employed for this study involved a thorough literature review spanning the years 2013 to 2023. The findings revealed that Tempe contains essential bioactive compounds such as isoflavones, saponins, and amino acids, all of which exhibit potent antioxidant, antihypertensive, and antidiabetic properties. Regular consumption of Tempe can play a crucial role in enhancing overall health and preventing various diseases. In conclusion, Tempe serves as an exemplary functional food option, offering immense health advantages to the Indonesian population. Its rich composition of bioactive compounds makes it a beneficial addition to the diet, promoting well-being and healthy living.